Pengujian Periode After-Ripening pada Beberapa Benih Padi (Oryza sativa L.) Varietas Unggul - Indria Rini, Sinta; Putri, Ria; Chrisna Pandu Pradana, Onny; Wahyudi, Anung (Politeknik Negeri Lampung, 2025)
Rice (Oryza sativa L.) plays a crucial role in Indonesia's food security. The use of high-quality seeds is essential to improve rice productivity. One of the factors affecting seed quality is seed physiology, particularly the physiological processes after harvest, known as after-ripening. After-ripening is a process that enables seeds to germinate after a certain period of dry storage. This study aims to determine the duration of the after-ripening period in several superior rice varieties and identify the variety with the shortest after-ripening period among those tested. The research was conducted at the Seed Analysis Laboratory, Lampung State Polytechnic, from November 2023 to January 2024, using a factorial Completely Randomized Design (CRD). The first factor was the after-ripening period (ranging from 0 to 6 weeks), and the second factor was the rice varieties (Gilirang, Inpari 42, and Inpari 43). Each experimental unit consisted of 100 rice seeds. Data were analyzed using ANOVA and further tested with Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the after-ripening period varied among the varieties. The Gilirang variety completed its after-ripening period within 1 week, while Inpari 42 and Inpari 43 required 2 and 3 weeks, respectively. The Gilirang variety demonstrated the shortest after-ripening period, than the Inpari 42 and Inpari 43 varieties.